An investigation of the HMGR gene and IPI gene expression in black caraway (Bunium persicum) - Darvishi Zeidabadi, Davod (3 Biotech, 2018)
Black caraway is of great importance for its terpene compounds. Many genes are involved in the biosynthesis of secondary metabolites in medicinal plants. For this study, black caraway seeds were collected from five different regions, i.e. [Isfahan; Kerman (Khabr); Semnan; Kerman (Sirch); and Hormozgan]. The black caraway seed oil was extracted and analyzed by means of the gas chromatography method. There was a negatively significant correlation (p ≤ 0.05) observed between cuminaldehyde and gammaterpinene compounds. 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGR) and isopentenyl pyrophosphate isomerase (IPI) play an important role in the biosynthesis of secondary metabolites. Appropriate primers were designed for these genes based on the conserved regions in other plants. Amplified fragments were then sequenced. Blastn results indicated the similarity of the high RNA sequences between new sequences and other HMGR and IPI gene sequences in GenBank, and it also identified the HMGR and IPI gene sequences of B. persicum. A fragment of the HMGR gene with KJ143741 number was recorded in the gene bank. Quantitative PCR showed that the relative expression of two genes in different growth stages of B. persicum was significantly different between the germination stage and the multi-leaf stage, and also between the germination stage and the flowering stage (p < 0.05); however, there was no significant difference observed between the flowering stage and the multi-leaf stage. The results indicated that the expression of HMGR increased from the germination stage to the adult plant, and then it got stable until the flowering stage; in the same vein, the expression of IPI increased continuously from the germination stage to the flowering stage. The expression of HMGR and IPI genes occurred differently at the germination stage of five ecotypes. The Hormozgan ecotype showed the least expression rate.